Review of the genus Dacne Latr. (Coleoptera, Erotylidae) from Kazakhstan - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2022)
Pleasing fungus beetles Dacne bipustulata (Thunberg, 1781), D. pontica (Bedel, 1868), and D. semirufula (Reitter, 1897) from the family Erotylidae are firstly recorded in Kazakhstan. The data on the Erotylidae fauna of this genus fromthree protected areas of Almaty oblast are given. D. semirufula is recorded only in Almaty city and its neighborhoods. It is possible that it is adventive, the introduction took place relatively recently, and the beetle did not have time to settle outside the site of invasion. A key to known species of the genus Dacne from Kazakhstan is given. Information about some species of mushrooms, on which Erotylidae were collected, presented for the first time. Pholiota vernalis (Saccardo) A.H. Smit & Hesler, 1968, Psathyrella candolleana (Fries) Maire, 1913 and Gloeophyllum sepiarium (Wulfen) P. Karsten, 1882 were recorded from Kazakhstan for D. bipustulata, Pholiota vernalis (Saccardo) A.H. Smit & Hesler, 1968 and P. candolleana for D. pontica and Fomitopsis betulina (Bulliard) B.K. Cui, M.L. Han & Y.C. Dai, 2016 and Ganoderma applanatum (Persoon) Patouillard, 1889 for D. semirufula.